Survival in Pandemic Times: Managing Energy Efficiency, Food Diversity, and Sustainable Practices of Nutrient Intake Amid COVID-19 Crisis - Geng, Jianli; Haq, Shamsheer Ul; Abbas, Jaffar; Ye, Hongwei; Shahbaz, Pomi; Abbas, Azhar; Cai, Yuyang (Frontiers in Environmental Science, 2022)
The COVID-19 pandemic led to an economic crisis and health emergency, threatening energy efficiency consumption, sustainable food diversity, and households' nutrition security. The literature documented that environmental threats can divert attention from renewable energy and food security challenges that affect humans' environmental behaviors. The COVID-19 crisis has consistently influenced environmental behaviors, as it primarily decreased income and disrupted food systems worldwide. This study investigated the COVID-19 consequences on household income, sustainable food diversity, sustainable energy consumption, and nutritional security challenges. The study used a self-structured online survey due to non-pharmaceutical restrictions and collected data from 728 households. The investigators applied t-test and logit regression to analyze the data for drawing results. Descriptive statistics show that COVID-19 has adversely affected the income of more than two-thirds (67%) of households. The pandemic has influenced households' food consumption, energy, and dietary patterns to safeguard their income. The t-test analysis indicated that households' food diversity and energy consumption significantly declined during the pandemic, and households consumed low-diversified food to meet their dietary needs more than twofold compared to pre-pandemic levels. The results showed that all nutrient consumption remained considerably lower in the COVID-19. Cereals are the primary source of daily dietary needs, accounting for over two-thirds of total energy and half of the nutrient consumption amid COVID-19. The share of vegetables and fruits in household energy consumption dropped by 40% and 30%. Results exhibited that increasing monthly income was inversely associated with worsening food diversity and intake with energy efficiency. Compared with farmers and salaried employment, wage earners were 0.15 and 0.28 times more likely to experience a decline in consuming food diversity. Medium and large households were 1.95 times and 2.64 times more likely than small to experience decreased food diversity consumption. Launching a nutrition-sensitive program will help minimize the COVID-19 impacts on energy consumption, food diversity, and nutritional security for low-income individuals. This survey relied on the recall ability of the households for the consumed quantities of food commodities, which may lack accuracy. Longitudinal studies employing probability sampling with larger samples can verify this study's insightful results.